Parenting in the age of social media: The buffering effect of parental self-efficacy on the relationship between parental social media use and parent child-relationship quality - Celeste Tipple; Cindy Branch-Smith (Acta Psychologica, 2025)
The widespread use of technology in daily life has raised concerns about its potential to disrupt social relationships, particularly within one of the most important human relationships: the parent-child relationship. This study assesses whether parental social media use (measured by a novel parental social media intensity scale) affects the parent-child relationship (measured by the child-parent relationship scale – short form), and whether parental self-efficacy (PSE, measured by the parenting sense of competence scale) moderates this effect. A cross-sectional, online survey study using correlational methods was utilised, with a final sample of 89 parents and caregivers (71.9 % women), averaging 42.6 years old (SD = 3.9). Contrary to expectations, parental social media use did not significantly influence the parent-child relationship, however, when parental social media use and PSE were included in the moderated multiple regression model, 53 % of the variance parent-child relationship quality was explained. Further, the moderation hypothesis proposing that higher levels of PSE weaken the negative impact of parental social media use on the parent-child relationship, was supported. These results highlight the critical role of PSE in mitigating the negative effects of high parental social media use on the parent-child relationship for parents with average or higher levels of PSE. Crucially, these findings have important implications for parents with low PSE and high social media use, who reported the lowest parent-child relationship within the sample.